Management of Social Media as One of The Arabic Language Learning Media in The Millennial Era - Muflikhah, Siti (International Conference of Moslem Society, 2019)
Social media is an online media that is used as a means of communication and social interaction through the internet. Someone can easily connect with other people, both those that have been known before and not yet known, either through written messages or talking directly listening to the voice, even through video calls. From social media someone can get the latest information quickly and easily, in the form of news, images, or videos. In this millennial era, the ease of social media has made most people feel the need and motivation to use it. For the world of education, social media can also be used as one of the learning media. Because the goals of social media include self-actualization, forming a community, establishing personal relationships, and marketing media. And the characteristics of social media include user participation, openness, conversation, and connectedness. Learning media in general is a tool for teaching and learning. Everything that can be used to stimulate thoughts, feelings, attention and abilities or skills of students so that it can encourage the learning process. Examples of learning media are audio media and graphic or visual media. In Arabic language lessons, the use of social media as one of the learning media is very supportive and very appropriate to increase learning or development outside of school hours. Management of social media can be used to add lessons about conversations, searching for vocabulary, and translating text. With other social media, it can be used to practice conversations both in writing and orally, practice reading, and so on. So that the learning media becomes fun and in accordance with the times.